Decision of the firm's vertical boundaries: Considerations on complementarity - Fortes, Bianca Jupiara; Souza, José Paulo de (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
The study aimed to present as an approach guided by propositions of complementarity of the theories TCT - Transaction Costs; MTC - Measurement Costs; RBV -Resource Based View, can support the understanding of the adoption of the vertical integration governance structure. We sought to propose a theoretical scheme, with qualitative methodology along with the concept of complementarity. It was found that the transaction of highly specific assets (TCT) and the measurement difficulty (MCT) justify vertical integration, but the theory of RBV points out that the choice of agents also depends on the availability of capacities and resources. The aim was to formulate this theoretical proposition so that it can be considered empirically in the most varied production chains.